Masochist or Murderer? A Discourse Analytic Study Exploring Social Constructions of Sexually Violent Male Perpetrators, Female Victims-Survivors and the Rough Sex Defense on Twitter - Sowersby, Chelsea-Jade; Erskine-Shaw, Marianne; Willmott, Dominic (Frontiers in Psychology, 2022)
‘Rough sex’ can be considered an act of sexual violence that is consensual or non-consensual, often resulting in bodily harm and in rare cases, fatalities. The rough sex defence is typically advanced by male perpetrators in an effort to portray a sexual encounter as consensual, to avoid criminal sanctions for causing injury or death. Public attitudes towards this defence are often reflected on social media following high profile cases and appear to echo dominant discourses that reinforce widely held sexual violence stereotypes. Therefore, this study aims to deconstruct public attitudes surrounding the rough sex defence. Namely, how female victims/survivors and male perpetrators of sexual violence are constructed online, whilst exploring the wider implications upon society. NVivo12 NCapture software was used to collect a sample of 1000 tweets mentioning the terms ‘rough sex’ or ‘rough sex defence’. Data were examined using Feminist Critical Discourse Analysis (FCDA), underpinned by a social constructionist perspective, to elicit emergent discourses. Findings indicate that Twitter allowed women to resist harmful victim-blaming discourses and constrained binary identities. Opposingly, men were constructed as sexually entitled predators, yet resisted these subject positions by advocating support for male victims/survivors. Additional analyses examine account holders’ constructions of British Parliamentarians (MP’s) and their campaigns against the rough sex defence. These constructions demonstrated a cultural, heteronormative and victim-blaming understanding of sexual violence, which calls for legislative clarity.